DELIVERY SERVICE AS COMPETITIVE STRATEGY - Schmidt Urdanivia, Johannes (2015)
Currently, managers in Peru have been obliged to use strategies to create value in their organizations and be competitive in a dynamic market, using the delivery service as a means of changing the business-customer relationship, changing the business model of many companies and obtaining benefits for both parties. This article discusses the delivery in important companies, showing the main features of this strategy and the benefits of its application.